The potential and economic viability of wind farms in Zimbabwe. Issue 15 (8th December 2019) - Samu, Remember; Fahrioglu, Murat; Ozansoy, Cagil
ABSTRACT: Wind energy potential in Zimbabwe so as to curb for the energy deficit is assessed in this study. The frequency of load shedding in Zimbabwe has increased; this is due to insufficient energy generation and rising energy demand. Wind energy is intermittent and these fluctuations might lead to an unreliable system so the wind turbines are going to be grid-connected, in the event of a deficit from the wind system, the grid will supply. Conversion of wind resources in 28 different locations scattered all over Zimbabwe into electrical energy is the main objective of this study. The study shows the energy production cost ranges from US$77.23/MWh to US$129.46/MWh. This kind of range will allow wind energy to be used in the future energy plans of Zimbabwe. Integration of renewable energy resources to increase the generation capacity does not only increase the energy production but also ensures a cleaner energy generation mix which is environmentally friendly.